Use of Imaging Modalities in Real Life: Impact on Visual Acuity Outcomes of Ranibizumab Treatment for Neovascular Age-Related Macular Degeneration in Germany - Joachim Wachtlin; Georg Spital; Steffen Schmitz-Valckenberg; Sandra Liakopoulos; Jessica Vögeler; Bettina Müller; Focke Ziemssen; Ocean study group (Journal of Ophthalmology)
Background. To date, there are limited prospective real-world data on the impact of optical coherence tomography (OCT) diagnostics on treatment outcomes in neovascular age-related macular degeneration (nAMD). Therefore, the prospective, noninterventional OCEAN study (NCT02194803) evaluated the use of OCT imaging and its impact on functional outcomes in Germany. Methods. The use of OCT imaging for treatment decisions was documented in nAMD patients receiving intravitreal ranibizumab injections at 347 study centres. Best-corrected visual acuity (BCVA) testing and treatment were performed according to routine clinical practice and documented over 24 months. Results. The majority of the 3,631 nAMD patients (59.6%) received a combination of OCT and fluorescein angiography imaging within the first 6 months. Over the remaining study course, this combination was used infrequently (range: 7.6% to 13.4%) and continually decreased over time; most patients received only OCT examinations (range: 48.9% to 52.5%; median: 3 within 12 months and 4 within 24 months). Subgroups according to the number of OCT examinations (≤4, rarely OCT examined; 5–8, moderately OCT examined; ≥8, well monitored) were associated with different treatment frequencies and outcomes: Rarely OCT-examined patients had received a median of 4 injections (range: 1–19) at 24 months; well-monitored patients had received a median of 8 injections (range: 1–21) at 24 months. Rarely OCT-examined patients had a mean change of BCVA of −0.3 letters (±26.1) at 24 months (n = 165); well-monitored patients showed a change of +2.0 letters (±20.8) at 24 months (n = 249). Time-to-response was greater for rarely examined than well-monitored patients, while duration-of-response was similar. Conclusion. Low number of visits as well as high number of treatment decisions without the use of OCT may contribute to undertreatment and poorer functional outcomes in patients undergoing ranibizumab treatment for nAMD in Germany. One potential reason for this could be that OCT was not covered by insurance for all patients during the study.